Effect of annealing temperature on K-shell X-ray fluorescence parameters of zinc oxide thin films prepared by the sol-gel method. Issue 2 (7th February 2019) - Sirin, Murat; Baltas, Hasan; Kiris, Erkan; Keskenler, Eyup Fahri
Abstract: Zinc oxide thin films were grown on a glass substrate by a sol-gel process using a spin-coating technique. The obtained thin films were annealed between 350 °C and 550 °C in 50 °C steps and were then characterized using X-ray diffraction, scanning electron microscopy, and X-ray fluorescence techniques. The samples were stimulated by 59.5 keV gamma rays emitted from an Americium-241 annular radioisotope source. K X-rays emitted by samples were counted using an ultra-low energy germanium detector with a resolution of 150 eV at 5.96 keV. It was found that there was generally a decrease in both the Kβ / Kα X-ray intensity ratios and the K X-ray fluorescence cross sections for zinc oxide between 350 °C and 500 °C, but not at 550 °C. In addition, the X-ray diffraction patterns of the films showed that the transition phase from an amorphous to a polycrystalline hexagonal wurtzite structure was complete at an annealing temperature of 500 °C. The results show that variations in these parameters can be explained by the reorganization of atoms and the charge transfer process due to the effect of the annealing temperature on the elements forming the compounds.